A Facultative Electroactive Chromium(VI)-Reducing Bacterium Aerobically Isolated From a Biocathode Microbial Fuel Cell - Wu, Xiayuan; Ren, Xiaoqian; Owens, Gary; Brunetti, Gianluca; Zhou, Jun; Yong, Xiaoyu; Wei, Ping; Jia, Honghua (Frontiers in Microbiology, 2018)
A facultative electroactive bacterium, designated strain H, was aerobically isolated from the biocathode of a hexavalent chromium (Cr(VI))-reducing microbial fuel cell (MFC). Strain H is Gram-positive and rod shaped (1–3 μm length). 16S rRNA gene analysis suggested that this strain (accession number MH782060) belongs to the genus Bacillus and shows maximum similarity to Bacillus cereus whose electrochemical activity has never previously been reported. Moreover, this strain showed efficient Cr(VI)-reducing ability in both heterotrophic (aerobic LB broth) and autotrophic (anaerobic MFC cathode) environments. Cr(VI) removal reached 50.6 ± 1.8% after 20 hours in LB broth supplemented with Cr(VI) (40 mg/L). The strain H biocathode significantly improved the performance of the Cr(VI)-reducing MFC, achieving a maximum power density of 31.80 ± 1.06 mW/m2 and Cr(VI) removal rate of 2.56 ± 0.10 mg/L·h, which were 1.26 and 1.75 times higher than those of the MFC with the sterile control cathode, respectively. This study offers a novel Gram-positive Bacillus sp. strain for Cr(VI) removal in MFCs, and shows a facile aerobic isolation method could be used to screen facultative electroactive bacteria.